Pengaruh Orientasi Kewirausahaan dan Orientasi Pasar Terhadap Inovasi Produk dan Kinerja Perusahaan (Usaha Mikro Kecil Kabupaten Bandung Barat) - Rari Ulima Fitri (Jurnal Riset Bisnis dan Investasi, 2021)
The performance of SMEs determine the level of gross domestic product. The COVID-19 pandemic has impacted the performance of MSMEs but it can be improved through product innovation. This study aims to analyze the effect of entrepreneurial orientation and market orientation on product innovation and firm performance. The research method used is explantory survey to reveal the correlation and influence between research variables. The data collection technique used a questionnaire with respondents of micro and small businesses in West Bandung Regency with a sample size of 50 companies. Hypothesis testing using Structural Equation Modeling (SEM) based on variants processed using Partial Least Square (PLS) applications. The results show that entrepreneurial orientation has a positive effect on market orientation, market orientation has a positive effect on product innovation, product innovation has a positive effect on company performance, entrepreneurial orientation has an indirect effect on product innovation through market orientation.